A ROLE OF MEDICAL REPRESENTATIVE IN PHARMACEUTICAL INDUSTRY - SURESH KUMAR, A.; KAVITHA, .S.FABIYOLA (International Journal of Psychosocial Rehabilitation, 2019)
This research study contents information about the medical representative’s role to develop business in pharmaceutical industry. It gives information about roles of medical representative to develop their customer, market, product, and implementation in pharmaceutical industry